Causes of Energy Wastage in Cloud Data Centre Servers : A Survey - Mosoti Derdus, Kenga; Oteke Omwenga, Vincent; Ogao, Patrick Job (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2019)
Datacenters are becoming the indispensable infrastructure for supporting the services offered by cloud computing. Unfortunately, datacenters consume a lot of energy, which currently stands at 3% of global electrical energy consumption. Consequently, cloud service providers (CSP) experience high operating costs (in terms of electricity bills), which is, in turn, passed to the cloud users. In addition, there is an increased emission of carbon dioxide to the environment. Before one embarks on addressing the problem of energy wastage in a datacenter, it is important to understand the causes of energy wastage in datacenter servers. In this paper, we elaborate on the concept of cloud computing and virtualization. Later, we present a survey of the main causes of energy wastage in datacenter servers as well as proposed solutions to address the problem.
Keywords: Cloud Computing; Datacenter; Data Centre Energy Wastage; Virtualization